2013
DOI: 10.1159/000346095
|View full text |Cite
|
Sign up to set email alerts
|

Purity and Stability of Online-Prepared Hemodiafiltration Fluid after Storage

Abstract: Background/Aims: Previous studies have suggested that online hemodiafiltration (OL-HDF) fluid can be used as dialysate for continuous renal replacement therapies, and thus HDF costs can be reduced. The aims of this study were to determine the purity of OL-HDF fluid and to verify the stability of the electrolyte composition and acid-base balance during its storage. Methods: OL-HDF fluid was collected in 70 individual bags and stored for up to 7 days. The following tests were performed daily in 10 bags: natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Using IHD machines to locally produce CKRT fluid is uncommon but not entirely novel [ 25 28 ]. The Cleveland Clinic, for example, has produced their own CKRT solutions using IHD machines for decades [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using IHD machines to locally produce CKRT fluid is uncommon but not entirely novel [ 25 28 ]. The Cleveland Clinic, for example, has produced their own CKRT solutions using IHD machines for decades [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corradi et al similarly produced online-prepared hemodiafiltration fluid and demonstrated stable clinical electrolyte composition (sodium, potassium, chloride, and calcium), did not identify macrocrystalization (despite changes in pH and P co 2 ), and had negative fluid cultures, endotoxin, and molecular testing after 7 days of storage. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Corradi et al, 5 evaluating a similar method, also showed no clinically relevant change in electrolytes over a much longer storage period, 96 hours, and assert lack of clinically relevant change to 168 hours. In any case, most CVVHD treatments involve frequent blood chemistry monitoring, and the effect of even major electrolyte deficits in the fluid would probably be detected long before adverse clinical impact.…”
mentioning
confidence: 99%